The development of knowledge management implementation at the Financial and Development Supervisory Agency (BPKP) - Wijaya, Andhika Pratama Tirta; Kutanegara, Pande Made; Djunaedi, Achmad (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2023)
The Financial and Development Supervisory Agency (BPKP), a pivotal public sector entity tasked with internal audit functions, recognizes the paramount importance of effectively managing auditors' experience and expertise. This study aims to delineate the Knowledge Management (KM) implementation stages within BPKP, a topic scarcely explored in Indonesian public-sector research. This study uses an abductive approach with a case study method by explaining a series of events over time with theory-based analysis. The results showed that the KM implementation in BPKP was carried out in four stages: preparation at the local level by conducting change management, work culture development, and initial research; implementation at the local level; implementation at the national level with a focus on the development of process, human, and technology aspects; and national development focuses on laying the groundwork for KM culture. There are KM implementation steps carried out by BPKP but not explained in the theory proposition: change management and developing a work culture that supports KM processes, initial research, benchmarking, and KM implementation regulations. BPKP needs to assess the maturity level of KM to determine the focus areas that need to be improved. This study contributes conceptually to KM frameworks tailored for public sector entities.